Heterosis in Simmental Angus rotational-cross calves - Kriese, L.A.; Schalles, R.R.; Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Heterosis estimates were determined for gestation length, birth weight, and yearling weight using a two-breed rotational crossbreeding system with Angus and Simmental cattle. Heterosis for gestation length was -.3%; birth weight, 8.31%; weaning weight 5.05%, and yearling weight, 5.39%. Angus-sired calves from Simmental darns were significantly heavier at weaning and as yearlings than the reciprocal cross.
Keywords: Beef; Heterosis; Gestation length; Birth weight; Yearling weight